Barcelona´s indianas manufacture: an early management accounting in J.B. Sires & Co. (1769-1805) - Rossi, Roberto (De Computis, Revista Española de Historia de la Contabilidad., 2017)
The paper aims to contribute to the debate about the emergence and development of management accounting in Europe by presenting an example of management accounting in Spain in the second half of the eighteenth century. The paper deepens the case of an indianas (cotton canvas printed and dyed) factory in Barcelona, exploring the productive organization and managerial structure using the accounting books of the firm. The firm’s methods of production, work organization, product costing, and production quality control are reviewed within the political and economic context of Spain during a period of deep transformation with the enthronement of a new monarchy and a deep change in the economic policy. The evidence presented in the paper support the existence of rudimentary management accounting and control techniques in a private firm in the midst of European industrialization.